Fibroblast growth factor-20 increases the yield of midbrain dopaminergic neurons derived from human embryonic stem cells - Correia, Ana Sofia; Anisimov, Sergey V.; Roybon, Laurent; Li, Jia-Yi; Brundin, Patrik (Frontiers in Neuroanatomy, 2007)
In the central nervous system, fibroblast growth factor (FGF)-20 has been reported to act preferentially on midbrain dopaminergic neurons. It also promotes the dopaminergic differentiation of stem cells. We have analyzed the effects of FGF-20 on human embryonic stem cells (hESCs) differentiation into dopaminergic neurons. We induced neuronal differentiation of hESCs by co-culturing those with PA6 mouse stromal cells for 3 weeks. When we supplemented the culture medium with FGF-20, the number of tyrosine hydroxylase (TH)- expressing neurons increased fivefold, from 3% to 15% of the hESC-derived cells. The cultured cells also expressed other midbrain dopaminergic markers (PITX3, En1, Msx1, and Aldh1), suggesting that some had differentiated into midbrain dopaminergic neurons. We observed no effect of FGF-20 on the size of the soma area or neurite length of the TH-immunopositive neurons. Regardless of whether FGF-20 had been added or not, 17% of the hESC-derived cells expressed the pan-neuronal marker b-III-Tubulin. The proportion of proliferating cells positive for Ki-67 was also not affected by FGF-20 (7% of the hESC-derived cells). By contrast, after 3 weeks in culture FGF-20 significantly reduced the proportion of cells undergoing cell death, as revealed by immunoreactivity for cleaved caspase-8, Bcl-2 associated X protein (BAX) and cleaved caspase-3 (2.5% to 1.2% of cleaved caspase-3-positive cells out of the hESC-derived cells). Taken together, our results indicate that FGF-20 specifically increases the yield of dopaminergic neurons from hESCs grown on PA6 feeder cells and at least part of this effect is due to a reduction in cell death.